2016
DOI: 10.1111/pce.12810
|View full text |Cite
|
Sign up to set email alerts
|

Function of Sitka spruce stone cells as a physical defence against white pine weevil

Abstract: Stone cells are a physical defence of conifers against stem feeding insects such as weevils and bark beetles. In Sitka spruce, abundance of stone cells in the cortex of apical shoot tips is associated with resistance to white pine weevil. However, the mode of action by which stone cells interfere with growth and development of weevil larvae is unknown. We developed a bioassay system for testing potential effects of stone cells, which were isolated from resistant trees, on weevil larvae. Bioassays using artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 22 publications
0
60
0
Order By: Relevance
“…Because terpenoids have negative effects on attacking bark beetles (Erbilgin et al 2006;Wallin and Raffa 2000;Zhao et al 2011b), these results suggest that Sitka and Lutz spruce are equally or more suitable hosts for the beetles than Norway spruce. However, host suitability to the spruce bark beetle is probably also influenced by physical or chemical characteristics of the bark that we did not quantify, such as the abundance of stone cells and the concentration of nutrients and secondary metabolites other than terpenoids (Schiebe et al 2012;Whitehill et al 2016). …”
Section: Constitutive Terpenoid Chemistry and Host Suitabilitymentioning
confidence: 99%
“…Because terpenoids have negative effects on attacking bark beetles (Erbilgin et al 2006;Wallin and Raffa 2000;Zhao et al 2011b), these results suggest that Sitka and Lutz spruce are equally or more suitable hosts for the beetles than Norway spruce. However, host suitability to the spruce bark beetle is probably also influenced by physical or chemical characteristics of the bark that we did not quantify, such as the abundance of stone cells and the concentration of nutrients and secondary metabolites other than terpenoids (Schiebe et al 2012;Whitehill et al 2016). …”
Section: Constitutive Terpenoid Chemistry and Host Suitabilitymentioning
confidence: 99%
“…Stone cells have a high predictive power of weevil resistance in Sitka spruce (King et al ., ). Stone cells are hypothesized to be a durable quantitative defense that provides resistance to several spruce species against bark beetles and weevils (Wainhouse et al ., ; King et al ., ; Whitehill et al ., ,b). Experiments with weevils on an artificial diet showed that SC function as a feeding barrier against larvae, disrupting their establishment, development and survival (Whitehill et al ., ,b).…”
Section: Introductionmentioning
confidence: 97%
“…Additional oleoresin terpene biosynthesis is induced by wounding or insect attack as part of the development of traumatic resin ducts in the cambium and xylem (Franceschi et al ., ; Martin et al ., ; Miller et al ., ; Zulak et al ., ). Physical defenses of conifers include bark texture and thickness, calcium oxalate crystals, and stone cells (SC, sclereids) (Franceschi et al ., ; King et al ., ; Whitehill et al ., ,b). The contribution of a specific defense mechanism to insect resistance and possible interactions of different defenses, are difficult to dissect in conifers when genetic mutants are not available.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations